Estudio de cooperación entre Colombia y Corea del Sur en el sector textil-confecciones. (2012)
This article identifies business opportunities in the Textile Clothing industry; between Colombia and South Korea. To this end; we analyze the international flow of raw materials and finished goods between these economies. It is also considered the innovation output (expressed through their national and international patents) and includes several interviews with industry experts.